Assortment and the evolution of cooperation in a Moran process with exponential fitness. (21st November 2016) - Cooney, Daniel; Allen, Benjamin; Veller, Carl
Abstract: We study the evolution of cooperation in a finite population interacting according to a simple model of like-with-like assortment. Evolution proceeds as a Moran process, and payoffs from the underlying cooperator–defector game are translated to positive fitnesses by an exponential transformation. These evolutionary dynamics can arise, for example, in a nest-structured population with rare migration. The use of the exponential transformation, rather than the usual linear one, is appropriate when interactions have multiplicative fitness effects, and allows for a tractable characterisation of the effect of assortment on the evolution of cooperation. We define two senses in which a greater degree of assortment can favour the evolution of cooperation, the first stronger than the second: (i) greater assortment increases, at all population states, the probability that the number of cooperators increases, relative to the probability that the number of defectors increases; and (ii) greater assortment increases the fixation probability of cooperation, relative to that of defection. We show that, by the stronger definition, greater assortment favours the evolution of cooperation for a subset of cooperative dilemmas: prisoners' dilemmas, snowdrift games, stag-hunt games, and some prisoners' delight games. For other cooperative dilemmas, greater assortment favours cooperation by the weak definition, but not by the strong definition. We also show that increasing assortment expands the set of games in which cooperation dominates the evolutionary dynamics. Our results hold for any strength of selection. Abstract : Highlights: We model evolution as a Moran process with assortment. Assortment is governed by a single parameter r . The results of interactions accord to a cooperative dilemma. These game payoffs translate to fitnesses exponentially. Greater r favours cooperation for most cooperative dilemmas.